Precipitating and aggravating factors of acne: a cross-sectional study in a tertiary care hospital - Rahman, Nazia; Nawaz, U. M. Shah; Hassan, Kazi Imran; Chowdhury, Shifat; Jahan, Momotaj; Imran, Tasnuva; Shyam, Nayan Chandra; Ahmed, Hassan; Islam, M. Hasnainul; Dey, Dulal Kanti; Uddin, M. Kutub (International Journal of Research in Medical Sciences, 2025)
Background: Acne vulgaris is a common chronic inflammatory disorder of the pilosebaceous units, characterized by comedones, papules, pustules, nodules and scarring. It predominantly affects adolescents and young adults due to hormonal changes, increased sebum production, bacterial colonization (mainly Propionibacterium acnes) and genetic predisposition. Although not life-threatening, acne can lead to significant psychological distress and often requires medical or systemic therapy. To identify the precipitating and aggravating factors contributing to acne among patients attending a tertiary care hospital. Methods: This descriptive cross-sectional study was conducted in the Department of Dermatology and Venereology, Combined Military Hospital (CMH), Dhaka, from March to August 2022. A total of 1200 acne patients aged 11–45 years were selected using purposive sampling. After informed consent, data were collected through structured interviews and clinical examinations. Patients with systemic illness, on hormonal therapy or under current acne treatment were excluded. Data were analyzed using SPSS version 22. Results: Among 1200 participants, 59.1% were aged 16–20 years (mean age 20.58±5.18) and 77.5% were unmarried. The cheeks (85.8%) and forehead (75.8%) were the most affected sites. Oily skin (70.8%) and papular lesions (81.6%) predominated, with moderate severity in 59.2%. Pigmentation (71.6%) was the commonest sequela. Major aggravating factors included cosmetics (27.5%), topical steroids (26.6%), stress (24.1%), sunlight exposure (20%) and skin pricking (15%). Conclusions: Acne is more prevalent among young females. Family history, cosmetic and steroid use, stress, sunlight and hormonal fluctuations are major precipitating and aggravating factors.